2014
DOI: 10.1002/cpp.1899
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Psychotherapy Dropouts: A Multilevel Approach

Abstract: Analyses data from 296 patients at a private outpatient clinic in a routine practice setting (CBT). Completer/dropout definition: presence or absence of measurement battery at post-assessment. Focuses on change in therapy processes by investigating post-session reports. Finds that positive changes in self-esteem experiences is the most robust predictor of dropout, followed by ratings of clarification experiences and the global alliance. In line with recent dropout research, these process indicators might help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 45 publications
1
33
3
1
Order By: Relevance
“…These include greater clinical severity (e.g., more complex clinical pictures, more comorbid diagnoses, poorer functioning, personality disorders; see Barrett et al, 2008, andSwift &Greenberg, 2012, for review), lower satisfaction with treatment and poorer patient-reported therapeutic alliance (Barrett et al, 2008;Kegel & Flückiger, 2014;Renk & Dinger, 2002;Shamir, Szor, & Melamed, 2010;Wnuk et al, 2013), and lower socioeconomic status and younger age (see Barrett et al, 2008;Swift & Greenberg, 2012 for review). Findings regarding sex, education level, race/ethnicity, and negative attitudes toward treatment have been equivocal (Anestis, Finn, Gottfried, Arbisi, & Joiner, 2015;Barrett et al, 2008;Chisholm, Crowther, & Ben-Porath, 1997;Gilmore, Lash, Foster, & Blosser, 2001;Munley & Busby, 1994;Swift & Greenberg, 2012).…”
Section: Journal Of Clinical Psychology Xxxx 2016mentioning
confidence: 98%
See 1 more Smart Citation
“…These include greater clinical severity (e.g., more complex clinical pictures, more comorbid diagnoses, poorer functioning, personality disorders; see Barrett et al, 2008, andSwift &Greenberg, 2012, for review), lower satisfaction with treatment and poorer patient-reported therapeutic alliance (Barrett et al, 2008;Kegel & Flückiger, 2014;Renk & Dinger, 2002;Shamir, Szor, & Melamed, 2010;Wnuk et al, 2013), and lower socioeconomic status and younger age (see Barrett et al, 2008;Swift & Greenberg, 2012 for review). Findings regarding sex, education level, race/ethnicity, and negative attitudes toward treatment have been equivocal (Anestis, Finn, Gottfried, Arbisi, & Joiner, 2015;Barrett et al, 2008;Chisholm, Crowther, & Ben-Porath, 1997;Gilmore, Lash, Foster, & Blosser, 2001;Munley & Busby, 1994;Swift & Greenberg, 2012).…”
Section: Journal Of Clinical Psychology Xxxx 2016mentioning
confidence: 98%
“…On this note, past work on treatment attrition among other clinical populations highlights predictors of dropout that may be relevant to suicidal individuals. These include greater clinical severity (e.g., more complex clinical pictures, more comorbid diagnoses, poorer functioning, personality disorders; see Barrett et al, 2008, andSwift &Greenberg, 2012, for review), lower satisfaction with treatment and poorer patient-reported therapeutic alliance (Barrett et al, 2008;Kegel & Flückiger, 2014;Renk & Dinger, 2002;Shamir, Szor, & Melamed, 2010;Wnuk et al, 2013), and lower socioeconomic status and younger age (see Barrett et al, 2008;Swift & Greenberg, 2012 for review).…”
Section: Treatment Attrition Suicidal Individuals 89mentioning
confidence: 99%
“…After treatment discontinuation, remission is out of reach. Patients either transfer back to the depressed state or remit spontaneously (because treatment discontinuation is often associated with spontaneous or premature remission) [53,54]. In every state, each individual is at risk of all-cause mortality.…”
Section: Model Structurementioning
confidence: 99%
“… 3 Karyotaki et al (2015) Demographics Estimation of drop-out risk factors Hierarchical Poisson regression modeling Individual Patient Data Meta-Analysis: raw data from various trials were analyzed to identify drop-out risk factors for web-based interventions. 3 Kegel and Flückiger (2014) Self-esteem, mastery, clarification, global Alliance Treatment dropout Hierarchical regression Clients with lower levels of self-esteem, fewer clarifying experiences, and absence of therapeutic alliance are more likely to dropout. 3 Meulenbeek et al (2015) Socio-demographic, personal, and illness-related variables Treatment dropout Logistic regression Dropout estimation for clients with mild panic disorder.…”
Section: Applying the Framework To Published Researchmentioning
confidence: 99%
“…Using regression techniques, clinical researchers have been exploring Type 3 models, using predictors that were collected at baseline (pre-test) assessments (e.g., DeRubeis et al, 2014 ; Huibers et al, 2015 ; Karyotaki et al, 2015 ; Kegel and Flückiger, 2014 ; Meulenbeek et al, 2015 ), mental health questionnaire responses that were collected during treatment (e.g., Proudfoot et al, 2013 ; Van et al, 2008 ), or repeated measures of the therapeutic relationship between the patient and the therapists (e.g., Priebe et al, 2011 ). In these studies, researchers tend to focus more on the importance of individual predictors on a population level (i.e., risk factors), rather than on the predictive power of the model as a whole.…”
Section: Applying the Framework To Published Researchmentioning
confidence: 99%